2022
DOI: 10.3390/ani12213013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Scoring Systems in the Newborn Calf: An Overview

Abstract: A scoring system is an instrument that enables the scorers, including farmers, technicians, and veterinarians, to adopt a systematic approach for diagnosis or monitoring, as it decreases bias and confounding and increases objectivity. Practically, it is a number assigned to a patient that correlates with a probability that a diagnosis can be confirmed or that a specific outcome will follow. This article examines the clinical scores designed or adapted to bovine medicine that aim to assess newborn calf viabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Vitality is essential because it is closely related to neonatal mortality in the first four weeks of life [ 89 , 92 ]. In the case of water buffalo, studies have reported a mortality rate of 17.9–39.8% [ 6 , 93 ], and according to Mee [ 90 ], Holstein-Friesian calves whose rectal temperature at birth decreases from 39–39.5 °C to 38.5–39 °C during the first hour of life are considered as having good vitality, while a temperature drop from 39.5–40 °C to less than 38.5 °C is associated with poor vitality individuals.…”
Section: Intrinsic Factors Affecting the Temperature In The Newborn B...mentioning
confidence: 99%
See 2 more Smart Citations
“…Vitality is essential because it is closely related to neonatal mortality in the first four weeks of life [ 89 , 92 ]. In the case of water buffalo, studies have reported a mortality rate of 17.9–39.8% [ 6 , 93 ], and according to Mee [ 90 ], Holstein-Friesian calves whose rectal temperature at birth decreases from 39–39.5 °C to 38.5–39 °C during the first hour of life are considered as having good vitality, while a temperature drop from 39.5–40 °C to less than 38.5 °C is associated with poor vitality individuals.…”
Section: Intrinsic Factors Affecting the Temperature In The Newborn B...mentioning
confidence: 99%
“…In the case of water buffalo, there are no vitality scores applied during calving or to evaluate the fetus’s health, as was mentioned by Szenci [ 89 ] for Bos calves. However, current clinical scores designed to assess vitality in ruminants consider physiological parameters such as rectal temperature (RT), heart rate (HR), respiratory function, mucous membrane color, grimace responses (including head shake, corneal reflex, suckling reflex, tongue withdrawal, and pedal reflex), and hair coat appearance (e.g., grade of meconium stain) [ 89 , 92 ]. Likewise, latency to attain sternal recumbency, head righting, and standing up are relevant behaviors that lessen temperature drop ( Figure 2 ) [ 89 , 92 ].…”
Section: Intrinsic Factors Affecting the Temperature In The Newborn B...mentioning
confidence: 99%
See 1 more Smart Citation
“…For the first phase, despite copious literature on developmental biology of production animals (e.g. Dwyer 2003;Sangild et al 2013;Andersen et al 2016;Greenwood and Bell 2019;Špinka 2019), milestones for functional development do not appear to have been consolidated into indexes such as Apgar scores (Baxter et al 2008;Probo and Veronesi 2022) that extend beyond the first few hours of life. Rates of acquisition of periodicity (Rhodes et al 2022) andcomplexity (Wu et al 2020) in behavioural activity in the young may have roles as indicators of functional development in addition to more commonly used task-specific performances such as time to first ingestion of colostrum (Quesnel et al 2023).…”
Section: Functional Capacitymentioning
confidence: 99%
“…The incidence of neonatal diarrhea varies from country to country. The lowest values are reported in Sweden and Denmark (9.8 and 10.3%) ( Probo and Veronesi, 2022 ). In a former study carried out in Bavaria (Germany) we showed that about 37% of newborn calves developed diarrhea within the first 8 days of life ( Schwaiger et al, 2022 ).…”
Section: Introductionmentioning
confidence: 97%